STRATEGI PEMBELAJARAN AFEKTIF DALAM PEMBINAAN KECERDASAN EMOSIONAL PESERTA DIDIK DI KELAS IV SEKOLAH DASAR - Rini Indriani; Ana Nurhasanah; A. Syachruroji (STKIP Subang, 2023)
This research is based on the importance of emotional intelligence in students. Not only intellectual intelligence but emotional intelligence is equally important. In this study aims to provide an overview of the affective learning strategy of the consideration model in developing students' emotional intelligence and its impact. This study uses a descriptive qualitative approach, the data used are interviews, observations, and documentation. The subjects studied were teachers as homeroom teachers for class IV and students in class IV at SDN Citangkil Baru, Cilegon City. The result of this research is that the teacher's efforts in fostering emotional intelligence are the affective learning of the consideration model, namely the learning steps of the consideration model. The impact of the consideration model of affective learning is to improve students' social skills, inculcate an attitude of tolerance, increase positive mindsets such as being responsible, mutual cooperation, caring for one another.